Gefängnisklima und Veränderung - Naegeli, Andreas (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
Andreas Naegeli and Ueli Hostettler have worked together for many years, addressing a wide range of issues in the prison system. Their different backgrounds – practice and research – have provided complementary perspectives, with scientific findings repeatedly providing valuable impetus for practical work. The two have focused particularly intensively on the prison climate and its effects on rehabilitation, reintegration, and the well-being of inmates.Their central conviction has always been that inmates should be able to change and that prison should provide them with the framework to do so. (machine translation)